Biomechanics and injury risk factors during race walking - Song, Q.; Ding, Z.; Mao, D.; Zhang, V.; Sun, W. (ISBS - Conference Proceedings Archive (Konstanz), 2013)
The purpose of this study is to describe the biomechanical characteristics during race walking and identify whether the race walking rules could cause potential injury risks. Fourteen elite race walkers participated in this study. Rs-scan plantar pressure plate and three digital cameras were used to collect data during race walking and normal walking. Paired t-tests were used to detect the differences. The results showed that during race walking, the peak pressures of the lateral heel and medial heel, the displacements of the center of pressure, ankle dorsiflexion, plantarflexion, knee extension, hip adduction, foot eversion, ankle angular velocity, and average horizontal velocity were significantly larger than those during normal walking. The greater heel peak pressure and more ankle eversion may be the injury risks caused by the rules of race walking.